Systematic study of electronic structure and band alignment of monolayer transition metal dichalcogenides in Van der Waals heterostructures. (30th November 2016) - Zhang, Chenxi; Gong, Cheng; Nie, Yifan; Min, Kyung-Ah; Liang, Chaoping; Oh, Young Jun; Zhang, Hengji; Wang, Weihua; Hong, Suklyun; Colombo, Luigi; Wallace, Robert M; Cho, Kyeongjae
Abstract: Two-dimensional transition metal dichalcogenides (TMDs) are promising low-dimensional materials which can produce diverse electronic properties and band alignment in van der Waals heterostructures. Systematic density functional theory (DFT) calculations are performed for 24 different TMD monolayers and their bilayer heterostacks. DFT calculations show that monolayer TMDs can behave as semiconducting, metallic or semimetallic depending on their structures; we also calculated the band alignment of the TMDs to predict their alignment in van der Waals heterostacks. We have applied the charge equilibration model (CEM) to obtain a quantitative formula predicting the highest occupied state of any type of bilayer TMD heterostacks (552 pairs for 24 TMDs). The CEM predicted values agree quite well with the selected DFT simulation results. The quantitative prediction of the band alignment in the TMD heterostructures can provide an insightful guidance to the development of TMD-based devices.